An investigation into the use of four-bar linkage mechanism as actuator for hard-disk drive - Djamari, Djati Wibowo. (2013)
The actuator of a hard disk drive (HDD) requires a high bandwidth for fast response to achieve higher recording density. The bandwidth is governed by several factors with the main one being the first in-plane natural frequency of the actuator arm. This paper investigates a new design that can achieve higher actuator bandwidth without sacrificing the out-of-plane stiffness. The design is structurally different from a conventional actuator arm (standard HDD single-stage actuator) and achieves improvement in the first in-plane natural frequency.